Electrospun Polymer Materials with Fungicidal Activity: A Review - Nasko Nachev; Mariya Spasova; Nevena Manolova; Iliya Rashkov; Mladen Naydenov (Molecules, 2022)
In recent years, there has been special interest in innovative technologies such as polymer melt or solution electrospinning, electrospraying, centrifugal electrospinning, coaxial electrospinning, and others. Applying these electrokinetic methods, micro- or nanofibrous materials with high specific surface area, high porosity, and various designs for diverse applications could be created. By using these techniques it is possible to obtain fibrous materials from both synthetic and natural biocompatible and biodegradable polymers, harmless to the environment. Incorporation of low-molecular substances with biological activity (e.g., antimicrobial, antifungal) is easily feasible. Moreover, biocontrol agents, able to suppress the development and growth of plant pathogens, have been embedded in the fibrous materials as well. The application of such nanotechnologies for the creation of plant protection products is an extremely promising new direction. This review emphasizes the recent progress in the development of electrospun fungicidal dressings and their potential to be applied in modern agriculture.